Analysis of Students Entrepreneurial Interest In Agriculture Sector - Ridha Rizki Novanda (Cita konsultindo, 2023)
More agriculture and agricultural companies could be used, especially by students in the agricultural sector, to help Indonesia overcome its food issue. Therefore, entrepreneurship classes are essential for students to pursue their interests. Similar to this, raising student interest in a career as an entrepreneur in the agriculture industry is the first step in improving students' business management skills. As previously said, it is urgently necessary to increase entrepreneurial activity in the agriculture sector. So this research is important to be carried out in analyzing how the interest of students in the agricultural sector. The study was conducted in Indonesia by distributing 100 questionnaires online. The initial screening was carried out on students who have agricultural backgrounds in Indonesia with the criteria have received entrepreneurial courses. Based on the results of the analysis it was found that the majority of students had a high interest in entrepreneurial interest in the agricultural sector.